Catalan experience of deadoption of low-value practices in primary care. Issue 1 (24th March 2022) - Almazán, Cari; Caro-Mendivelso, Johanna Milena; Mias, Montse; Barrionuevo-Rosas, Leslie; Moharra, Montse; Gagnon, Marie-Pierre
Abstract : Reducing ineffective practices is one way to ensure high-quality and efficient healthcare for the population. For this reason, several initiatives have been implemented worldwide to reduce low-value care. This article describes the experience of the Essencial project, a multifaceted deadoption strategy implemented in the Catalan primary care system. Lessons learnt from this project include the importance of considering the local context in deadoption strategies, providing adequate training and communication material to patients and clinicians and supporting the key role of clinical champions. Given the knowledge gaps regarding the conditions for successful deadoption strategies, the Catalan experience could provide enlightenment on how to implement, evaluate and sustain a large-scale collaborative deadoption strategy in primary healthcare.